IL and information ethics: how to avoid plagiarism in scientific papers? - Hebrang Grgić, Ivana (2014)
Ethics is an important part of scientific communication. Not only authors, but reviewers, editors and publishers, have to be aware of all the ethical rules and practices, discouraging any attempt of misconduct. One of the most usual misconducts in scientific publishing is plagiarism. It has negative consequences for authors, editors and scholarly journals causing loss of credibility, reputation, and, therefore loss of readers and finances. Information literacy in that context implies knowledge of information evaluation, proper ways of quotation and citation of resources. Avoiding plagiarism has its roots in higher education – students have to be educated about the proper ways of using other persons’ ideas. By using modern technologies, plagiarism is easier than ever – the “copy-paste” practice is easy to use. Students have to be thought that the practice is great threat to proper professional and scientific communication. Plagiarism detection software can diminish the threat, but it is not the only way of controlling producers of scientific information. Academic ethics can be assured by proper education, good codes of ethics and detailed instructions to authors of scientific works. Accurate author’s guidelines in scholarly journals could help all the participants of scientific communication to avoid misconducts. The paper will analyse the content of author’s guidelines in Croatian journals in the field of information science, with the accent on citation guidelines. The sample will include all the journals that cover the field, as listed in the Hrčak portal (portal of Croatian scientific journals). The analysis will try to find out whether the journals (i. e. their publishers and editors) mention and/or explain plagiarism, ethics, authorship, prior publication and reference systems in their instructions to authors. The paper will also analyse content of codes of ethics of Croatian universities, with the accent on the parts concerning plagiarism (universities of Zagreb, Osijek, Pula, Rijeka, Split, Zadar and Dubrovnik). We expect to conclude about the use of proper protection mechanisms of Croatian academic community when it comes to misconducts, especially plagiarism, in publishing results of scientific work. In conclusion, a list of the most important steps in avoiding plagiarism in scientific papers will be given.
ENG